Participative model of democracy in the context of calculation of city socio-cultural space - Oleksenko, Roman; Олексенко, Роман Іванович; Олексенко, Роман Иванович; Afanasieva, L. (My University, 2020)
EN: The purpose of this study is to carry out a comprehensive analysis of community mapping tools as an effective means of identifying community potential, in co-operation with local governments to develop a strategy for its development in the context of modernizing the socio-cultural space of the Ukrainian city on a democratic basis. Methodology of research: The following general scientific and empirical methods such as: analysis, synthesis, comparison, systematization, generalization, as well as questionnaires, focus group research and the "World café" method were used for realization of the set tasks. To analyze the development and implementation of mapping projects of communities of the modern city, we have involved axiological, participatory and activity approaches. Own research and cartographic toolkit of the project "Mapping communities as a tool for implementation of the policy" The studying city "is developed. The scientific novelty of the research is interdisciplinary correlative-integrative approach to the study of the problem of mapping, modernization and sustainable socio-cultural development of the modern Ukrainian city, combining the cultural, philosophical and sociological principles of analysis and consists in an attempt of a culturallyanalytical comprehensive study of ways of organizing the cooperation of the city community with local self-government bodies. Conclusions. In general, by summarizing the use of the method of mapping communities as an effective mechanism of participatory democracy, it should be assumed that the practices of participatory governance in the broadest sense allow participants in the process not only to be informed, but also to promote consensus and legitimacy of institutional solutions for their implementation. Thus, the main thing is the process of greater involvement of the population in the form of delibrations for the public discussion of general problems and the legitimization of institutional decisions for their implementation. The result of participative management in the implementation of public policy is the construction of an open system of governance, by shifting paradigms: from management through impersonal institutions and officials, to collective public administration. UK: Метою даного дослідження є здійснення комплексного аналізу інструментів картування громад як дієвого засобу виявлення потенціалу громади, спільного з органами місцевого самоврядування вироблення стратегії його розвитку в контексті модернізаційного оновлення соціально-культурного простору українського міста на демократичних засадах. Методологія дослідження: для реалізації поставлених завдань були застосовані такі загальнонаукові та емпіричні методи, як: аналіз, синтез, порівняння, систематизація, узагальнення, а також анкетування, фокус-групове дослідження та метод «World café». Для аналізу розробок і втілення проектів картування громад сучасного міста нами задіяний аксіологічний, партисипативний і діяльнісний підходи. Розроблено власний дослідницький та картографічний інструментарій проекту «Картування громад як інструмент для впровадження політики «Місто, що навчається». Науковою новизною дослідження є міждисциплінарний корелятивно-інтегративний підхід до вивчення проблеми картування, модернізації та сталого соціокультурного розвитку сучасного українського міста, що поєднує культурологічний, філософський та соціологічний принципи аналізу й полягає у спробі культурологоаналітичного комплексного дослідження шляхів організації співпраці міської громади з органами місцевого самоврядування. Висновки. В цілому, узагальнюючи використання методу картування громад як дієвого механізму партисипативної демократії, слід вважати, що практики партисипативного управління в широкому сенсі, дозволяють учасникам процесу бути не тільки поінформованими, залученими, а й сприяти досягненню консенсусу і легітимності інституційних рішень для їх впровадження. Таким чином, головним є процес більшого залучення населения в формі делиберації для публичного обговорення загальних проблем та легітимація інституціональных рішень для їх впровадження. Результатом партисипативного управління в реалізації публічної політики є побудова відкритої системи управління, шляхом зміщення парадигм: від управління за допомогою знеособлених інститутів і чиновників, до колективного публічного управління. RU: Целью данного исследования является осуществление комплексного анализа инструментов картирования общин как действенного средства выявления потенциала общества, совместно с органами местного самоуправления выработки стратегии его развития в контексте модернизационного обновления социально-культурного пространства украинского города на демократических началах. Методология исследования: для реализации поставленных задач были применены следующие общенаучные и эмпирические методы, как: анализ, синтез, сравнение, систематизация, обобщение, а также анкетирование, фокус групповое исследование и метод «World café». Для анализа разработок и реализации проектов картирования общин современного города нами задействован аксиологический, партисипативный и деятельностный подходы. Разработан собственный исследовательский и картографический инструментарий проекта «Картирование общин как инструмент для внедрения политики «Город, который обучается». Научной новизной является междисциплинарный коррелятивно-интегративный подход к изучению проблемы картирования, модернизации и устойчивого социокультурного развития современного украинского города, который сочетает культурологический, философский и социологический принципы анализа и заключается в попытке культуроаналитического комплексного исследования путей организации сотрудничества городской общины с органами местного самоуправления. В целом, обобщая использования метода картирования общин как действенного механизма партисипативной демократии, следует считать, что практики партисипативного управления в широком смысле позволяют участникам процесса быть не только информированными, привлеченными, но и способствовать достижению консенсуса и легитимности институциональных решений для их внедрения. Таким образом, главным является процесс большего привлечения населения в форме делиберации для публичного обсуждения общих проблем и легитимация институциональных решений для их внедрения. Результатом партисипативного управления в реализации публичной политики является построение открытой системы управления путем смещения парадигм: от управления с помощью обезличенных институтов и чиновников, к коллективному публичному управлению.
Партисипативна модель демократії в контексті картування громад міського соціокультурного простору
Партисипативная модель демократии в контексте картирования сообщества городского социокультурного пространства
Keywords: democracy; society; political culture; freedom; community; демократія; суспільство; політична культура; свобода; громада; демократия; общество; политическая культура; сообщество